Trends in bilateral mastectomy for cases of unilateral breast cancer in a Brazilian institute over a 10-year period - Cavalcante, Francisco Pimentel; Silva, Paulo Goberlâneo de Barros; Lima, Marcos Venicio Alves (Mastology, 2021)
Introduction: There has been a substantial increase worldwide in the number of women with unilateral breast cancer who undergo bilateral mastectomy. Possible contributing factors include the advent of nipple-sparing mastectomy (NSM) and an improvement in breast reconstruction techniques. This study evaluated the trend in bilateral mastectomy at the Ceará Cancer Institute in Brazil. Methods: Patients with unilateral breast cancer who underwent mastectomy and immediate breast reconstruction were evaluated retrospectively between 2009 and 2018. Clinical, pathological and surgical factors were analyzed to determine their possible effects on the type of surgery performed. Results: Of 121 patients, 77 (63.6%) were submitted to unilateral mastectomy, while 44 (36.4%) underwent bilateral mastectomy. Most were treated with NSM (n = 66; 54.5%), with this technique being significantly associated with bilateral mastectomy (p < 0.001). Bilateral mastectomy increased significantly over the period (p = 0.009; r 2 = 0.592), but unilateral mastectomy did not (p = 0.417; r2 = 0.084). Age < 45 years (p = 0.007) and negative axilla (p = 0.003) were also associated with bilateral mastectomy, while axillary dissection was associated with unilateral mastectomy (p = 0.028). Multivariate analysis showed the 2016-2018 period to be an independent factor associated with bilateral mastectomy. Conclusions: These results corroborate the international literature. From 2010 onwards, there was a trend towards an increase in bilateral mastectomy with breast reconstruction. These data may contribute to multidisciplinary debates, facilitating the establishment of guidelines. Further studies are required to improve understanding of this phenomenon in Brazil.